2019
DOI: 10.1186/s13024-019-0344-2
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 Biology from structure to dysfunction: research progresses, but the themes remain the same

Abstract: Since the discovery of leucine-rich repeat kinase 2 (LRRK2) as a protein that is likely central to the aetiology of Parkinson’s disease, a considerable amount of work has gone into uncovering its basic cellular function. This effort has led to the implication of LRRK2 in a bewildering range of cell biological processes and pathways, and probable roles in a number of seemingly unrelated medical conditions. In this review we summarise current knowledge of the basic biochemistry and cellular function of LRRK2. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
153
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(154 citation statements)
references
References 216 publications
(307 reference statements)
1
153
0
Order By: Relevance
“…Since the abnormal enhancement of LRRK2 kinase activity is implicated in the PD-related LRRK2 mutants, including the most common G2019S mutation, extensive efforts have been devoted to the development of LRRK2 kinase inhibitors as potential therapeutic agents [10]. However, increasing evidence also highlights the functional significance of LRRK2 in various cellular processes in the brain and peripheral organs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the abnormal enhancement of LRRK2 kinase activity is implicated in the PD-related LRRK2 mutants, including the most common G2019S mutation, extensive efforts have been devoted to the development of LRRK2 kinase inhibitors as potential therapeutic agents [10]. However, increasing evidence also highlights the functional significance of LRRK2 in various cellular processes in the brain and peripheral organs.…”
Section: Discussionmentioning
confidence: 99%
“…8a, b). The PD-related G2019S missense mutation in LRRK2 kinase domain is generally regarded to cause an increase of LRRK2 kinase activity [10]. We next cultured SPNs from Lrrk2 G2019S homozygous KI (GS/GS) mice for 3 weeks and found that G2019S mutation caused a similarly substantial increase in nuclear size, with only a modest reduction in nuclear invaginations compared to controls (Fig.…”
Section: Lrrk2 −/− Mice Develop Age-dependent Motor Abnormalitiesmentioning
confidence: 93%
See 2 more Smart Citations
“…Lrrk2 encodes a ~280 kDa protein that contains multiple enzymatic domains and protein–protein interacting domains (Figure 1). These include armadillo‐like repeats (ARM), ankyrin repeats (ANK), leucine‐rich repeats (LRR), and a WD40 domain, which all function as sites for protein–protein interactions (Berwick, Heaton, Azeggagh, & Harvey, 2019). The enzymatic domains of Lrrk2 include the kinase domain and the GTPase domain, which is comprised of the Roc (Ras of complex protein) and COR (C‐terminal of Roc) domains (Langston, Rudenko, & Cookson, 2016).…”
Section: Introductionmentioning
confidence: 99%